(untitled) (American Journal of Islam and Society, 1989)
History is very important from the ideological and educational standpoint in addition to its importance as a discipline of knowledge and as information. The Qur’an teaches us, “Indeed in the stories of these men, there is a lesson for those who can think.” [12:111] Educationally, then, for the new generations and ideologically for those who are committed to Islam as a way of life, it is very important to get the message of history which enlightens us in dealing with contemporary circumstances. Some introductory remarks Is it more correct to say Islamic history or Muslim history? Each description has its pros and cons. When you say “Islamic history“ you care more about commitment to Islam and assessment accoding to Islamic criteria, since not everythtng which happened in the past or happens at present on the Islamic scene can really be considered Islamic. Historical events should be evaluated under such a term according to Islam whether they are social, cultural, political or economic. What may be positive in terms of a historical development or very important as a mere material accomplishment may or may not be something important from the viewpoint of Islam. Suppose that we have a very magnificent tomb made by Muslims, would you consider this Islamic or not? Calling our history “Muslim history“ may draw a line between human behavior and Islam itself. History represents the outcome of Muslim practices and each can be evaluated amrdmg to Islam. It is just a development of Muslim thinking and behavior- Muslim interaction with other human universal effects. Muslim history is the product of Muslims as human ...